Bubonic Plague Alert Based on Flea Index in The Plague Observation Area of Pasuruan District, East Java Year 2023 - Inayah, Zufra; Reza Fitri Yanti; Murti, Dewinta Risna; Setyowati, Wulan; Anggraeni, Desy Novita (Yayasan Ahmad Mansyur Nasirah, 2024)
Plague is a very serious health problem and can lead to outbreaks or epidemics caused by the bacterium Yersinia pestis. This study aims to determine the alertness of plague based on the flea index in the plague observation area in Pasuruan Regency, East Java. The research method used was exploratory. The research data used secondary data from the Surabaya Public Health Laboratory (BBLabkesmas). The plague observation area included four sub-districts. Tutur, Tosari, Puspo, and Pasrepan. The research variable was the index of fleas found in the observation area. Data were analyzed descriptively and presented in graphical form. The results showed that 2146 rats were caught in 2023, of which 630 were rats with fleas. The majority of rat species found were Rattus tanezumi (65.19%), Rattus exulans (22.51%), Hylomys suillus, shrew (Suncus murinus), and other rat species. The flea species found were Xenopsylla cheopis (78%) and Stivalius cognatus (22%). The two main indicators to measure the risk of plague transmission are the Generalized flea Index and the Specific flea Index. The generalized flea Index measures the density of fleas that are not the main vector of plague, while the Specific flea Index measures the density of Xenopsylla cheopis as the main vector of plague. In the Tutur sub-district, the first semester showed Ngaruh hamlet was alert with a specific flea Index of 1.22, but in the second semester, all areas in the Tutur sub-district were declared safe. Pasrepan and Puspo sub-districts were declared safe in both semesters. In the Tosari sub-district, first-semester Tosari Hamlet and second-semester Sedaeng Hamlet were declared alert with a specific flea Index of 1.06 and 1.04 respectively.